Timor-Leste : Public Investment Management from Post-Conflict Reconstruction to the 2011-2020 Strategic Development Plan - Rab, Habib; Petrie, Murray (World Bank, Washington, DC, 2015)
This chapter captures some of the Public Investment Management (PIM) lessons and experiences from Timor-Leste as it tried to meet urgent infrastructure demands in a post-conflict environment, which benefited from a surge in petroleum receipts. It looks at institutional changes using standard features of Public Investment Management systems starting from the immediate post-independence period in 1999 right up to the launch of Timor-Leste s Strategic Development Plan in July 2011. Increased control over domestic resources over this period, thanks to the onset of natural resource rents, gave the government more autonomy over prioritization and management of capital expenditure. It also enabled use of the Capital Budget to pursue multiple objectives including consolidating social stability, stimulating economic activity outside Dili, delivering quick results to address urgent infrastructure needs, and growth of the domestic private sector. The chapter tries to highlight some of the trade-offs that the PIM system faced in trying to meet these different objectives. It finally looks at some of the institutional reforms that the government embarked on in 2011 when the focus was shifting to large investments for long-term growth. This included centralizing selected PIM functions for large projects and decentralizing those functions for smaller projects.